Panorama das dissertações de educação matemática sobre o ensino superior da PUC/SP de 1994 a 2000 - Junho, Benedito Afonso Pinto (2003)
The aim of this work was to construct a map of the dissertations related to Higher Education produced in the Program of Post-Graduate Studies in Mathematics Education of the Pontifícia Catholic University of São Paulo throughout the 90s decade. Following the analysis of each of the ten dissertations studied, it was possible to categorize them according to the themes investigated and the methodologies used. The results obtained indicated that the majority of the studies concerned the teaching and learning of disciplines associated with pure mathematics and employed as a research strategy the elaboration and application of a didactic sequence based on the methodology of Didactic Engineering